2018
DOI: 10.1038/nature25741
|View full text |Cite
|
Sign up to set email alerts
|

Population snapshots predict early haematopoietic and erythroid hierarchies

Abstract: Red cell formation begins with the differentiation of multipotent hematopoietic progenitors. Reconstructing the steps of differentiation represents a stereotypical challenge in stem cell biology. Combining single-cell transcriptomics, fate assays, and theory for predicting fate from population snapshots, we inferred a continuous, hierarchical structure of murine hematopoietic progenitors committing to seven blood lineages. We uncovered coupling between erythroid and basophil/mast cell fates, a global hematopoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
433
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 325 publications
(479 citation statements)
references
References 70 publications
45
433
1
Order By: Relevance
“…This observation agrees with recent studies in mouse, human and zebra fish, that have shown that the HSPC pool is a particularly variable cell population, 7,9,10,12,13 and highlights the fact that classification accuracy will depend upon both the amount of data available for training and the heterogeneity intrinsic to the cell population being considered. This issue will also be important when we consider transferring mouse biology to the human.…”
Section: Mapping Biology From Mouse To Mansupporting
confidence: 91%
See 2 more Smart Citations
“…This observation agrees with recent studies in mouse, human and zebra fish, that have shown that the HSPC pool is a particularly variable cell population, 7,9,10,12,13 and highlights the fact that classification accuracy will depend upon both the amount of data available for training and the heterogeneity intrinsic to the cell population being considered. This issue will also be important when we consider transferring mouse biology to the human.…”
Section: Mapping Biology From Mouse To Mansupporting
confidence: 91%
“…Thirdly, it is well-established that cell types in the hematopoietic cell lineages of the BM are arranged according to a hierarchical structure. [9][10][11] By considering adjacency relationships between clusters, we were able to broadly recapitulate the known structure of this hierarchy, indicating that the clustering structure that we observed captures salient features of the mouse BM biology ( Fig. 1d).…”
Section: Mapping Biology From Mouse To Manmentioning
confidence: 58%
See 1 more Smart Citation
“…Clusters were identified using the "FindClusters" function and UMAP projection was generated using the "RunUMAP" function, both with the first 16 principle components. Seurat clusters were annotated using marker genes and by reference to previously published data 19 -Seurat identified two clusters corresponding to committed erythroid progenitors (CEP) and four clusters corresponding to cells undergoing erythroid terminal differentiation (ETD). Average gene expression for populations matching those obtained by FACS sorting was generated by using the "SubsetData" function to select cells with low levels of cell-surface barcodes corresponding to lineage markers, and appropriate levels of barcodes corresponding to CD71 and Ter119.…”
Section: Methodsmentioning
confidence: 99%
“…We used Tiled-C to study the changes in chromatin structure associated with gene activation in primary cells during erythroid differentiation. Using fluorescence-activated cell sorting (FACS), we isolated sequential stages of erythroid differentiation directly from mouse fetal livers 18,19 (Figure 3a,b). We focused our analysis on a ~3.3 Mb region containing the well-characterized a-globin genes and their associated regulatory elements.…”
mentioning
confidence: 99%